MiR-125b-5p ameliorates ox-LDL-induced vascular endothelial cell dysfunction by negatively regulating TNFSF4/TLR4/NF-κB signaling - Wenshuai He; Limin Zhao; Pengfei Wang; Maojia Ren; Yunfei Han (BMC Biotechnology)
Abstract Background Oxidized low-density lipoprotein (ox-LDL)-induced endothelial cell dysfunction plays a crucial role in the progression of atherosclerosis (AS). Although miR-125b-5p is known to be involved in cardiovascular and cerebrovascular disorders, its function in ox-LDL-induced endothelial injury is still not well understood. Methods An in vitro AS cell model was established by exposing human umbilical vein endothelial cells (HUVECs) to 100 µg/mL ox-LDL for 24 h. A series of functional assays, including CCK-8 assay, flow cytometry, MDA and SOD kits, capillary-like network formation assay and ELISA assay were performed in vitro. TNFSF4/TLR4/NF-κB pathway-related protein expressions were measured by Western blot. Molecular mechanisms were elucidated through quantitative real-time PCR, western blot analysis, and luciferase reporter assays. Results Our investigation revealed that exposure to ox-LDL led to a downregulation in miR-125b-5p, while upregulating the expression of tumor necrosis factor (ligand) superfamily, member 4 (TNFSF4), TLR4, p-p65 and p-IkBa in HUVECs in a dose-dependent manner. We confirmed TNFSF4 as a direct target of miR-125b-5p. Ox-LDL exposure led to decreased cell viability and angiogenic capacity, along with increased apoptosis, inflammation, and oxidative stress in HUVECs. These effects were reversed by overexpressing miR-125b-5p or knocking down TNFSF4. Overexpression of TNFSF4 significantly reversed the effects brought about by miR-125b-5p in HUVECs exposed to ox-LDL. Moreover, miR-125b-5p inactivated the TLR4/NF-κB signaling pathway by negatively regulating TNFSF4. Conclusions In summary, our findings demonstrate that miR-125b-5p possessed an anti-inflammatory and anti-apoptosis against ox-LDL-induced HUVEC injury by regulating the TNFSF4/TLR4/NF-κB signaling, indicating that miR-125b-5p may have an important therapeutic function for AS.